การพัฒนาหลักสูตรฝึกอบรมตามแนวคิดชุมชนแห่งการเรียนรู้เชิงวิชาชีพเพื่อส่งเสริมด้านนวัตกรรมเทคโนโลยีสารสนเทศและการสื่อสารของนักศึกษาวิชาชีพครู - จุลเนียม, นีรนาท; ฉัตรธีราโชติ, ธันยนันท์ (วารสารการบริหารการศึกษา มมร.วิทยาเขตร้อยเอ็ด; Vol 5 No 1 (2568): มกราคม – เมษายน 2568, 2025)
การวิจัยนี้มีวัตถุประสงค์เพื่อ 1) ศึกษาข้อมูลพื้นฐานความต้องการและจำเป็น 2) สร้างหลักสูตร 3) ทดลองใช้หลักสูตร และ 4) ประเมินหลักสูตร เป็นการวิจัยและพัฒนา โดยใช้พัฒนานักศึกษาวิชาชีพครู ชั้นปีที่ 4 มหาวิทยาลัยราชภัฏธนบุรี จำนวน 30 คน  ที่อาสาสมัครเข้าร่วมทำกิจกรรมพัฒนาหลักสูตร ในภาคเรียนที่ 1 ปีการศึกษา 2567 ระหว่างเดือนตุลาคม 2567 และทำการประเมินหลักสูตรด้านปัจจัยนำเข้า ด้านกระบวนการ และด้านผลผลิต เครื่องมือที่ใช้ในการวิจัย คือ แบบสำรวจ แบบวิเคราะห์เอกสาร แบบสัมภาษณ์แบบกึ่งโครงสร้าง แบบสรุปข้อมูล และแบบประเมินวิเคราะห์ข้อมูลโดยค่าเฉลี่ย ส่วนเบี่ยงเบนมาตรฐาน การทดสอบค่าที การวิเคราะห์เนื้อหา และสรุปข้อมูล ผลการวิจัยพบว่า 1. ผลการศึกษาข้อมูลพื้นฐานที่จำเป็นพบว่า การปฏิบัติการสอนของครูไม่สามารถเป็นแบบอย่างที่ดีได้ และครูมีความต้องการส่งเสริมด้านนวัตกรรมเทคโนโลยีสารสนเทศและการสื่อสาร และการเรียนรู้การจัดบรรยากาศในชั้นเรียน การประเมินผลการเรียนรู้จากการจัดการ เรียนรู้เชิงวิชาชีพ โดยผ่านการสำรวจและวิเคราะห์ปัญหา การวางแผน การปฏิบัติตามแผน การสังเกตการปฏิบัติงานทำงานของผู้บริหารสถานศึกษาและครู การสะท้อนผลการปฏิบัติงาน และเปิดโอกาสให้ผู้มีส่วนเกี่ยวข้องกับการเรียนการสอนสะท้อนผลการปฏิบัติงาน ของนักศึกษาวิชาชีพครูในโรงเรียนและเกิดผลลัพธ์เชิงประจักษ์แก่ผู้เรียน 2. หลักสูตรฝึกอบรมตามแนวคิดชุมชนแห่งการเรียนรู้เชิงวิชาชีพเพื่อส่งเสริมด้านนวัตกรรมเทคโนโลยีสารสนเทศและการสื่อสารของนักศึกษาวิชาชีพครู มี 6 องค์ประกอบ ได้แก่ 1) หลักการ 2) จุดมุ่งหมาย 3) เนื้อหาสาระ 4) วิธีการที่ใช้ในการฝึกอบรม 5) สื่อที่ใช้ในการฝึกอบรม 6) การวัดและการประเมินผล โดยดำเนินการกิจกรรม 5 ขั้นตอน โดยได้หลักสูตรมีความเหมาะสมอยู่ในระดับมาก ผลการนำหลักสูตรไปใช้นำร่อง (tryout) ครูมีการจัดการเรียนรู้เชิงวิชาชีพสูงกว่าเกณฑ์ร้อยละ 75 ที่กำหนดไว้อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 3. ผลการทดลองใช้หลักสูตรฯ หลังการใช้หลักสูตรฝึกอบรม พบว่า ครูมีการจัดการเรียนรู้เชิงรุกอยู่ในระดับคุณภาพดีเยี่ยมและสูงกว่า เกณฑ์ร้อยละ 75 ที่กำหนดไว้อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 4. ผลการประเมินหลักสูตร ความคิดเห็นของครูที่มีต่อหลักสูตรฝึกอบรมตามแนวคิดชุมชนแห่งการเรียนรู้เชิงวิชาชีพเพื่อส่งเสริมด้านนวัตกรรมเทคโนโลยีสารสนเทศและการสื่อสารของนักศึกษาวิชาชีพครู ด้านปัจจัยนำเข้า ด้านกระบวนการ และด้านผลผลิต โดยรวมอยู่ในระดับมากที่สุด This research aimed to 1) study the basic information of needs and necessity,    2) create a curriculum, 3) test the curriculum, and 4) evaluate the curriculum. It is a research and development using 30 fourth-year teaching students at Thonburi Rajabhat University who volunteered to participate in the curriculum development activity in the first semester of the academic year 2024 during October 2024 and evaluate the curriculum in terms of inputs, processes, and outputs. The research instruments used were a survey, a document analysis form, a semi-structured interview form, a data summary form, and an evaluation form for analyzing data by mean, standard deviation, t-test, content analysis, and data summary. The research results found that: 1. The results of the study of the necessary basic information found that teachers' teaching practices could not be good examples. Teachers need to promote innovation in information and communication technology and classroom atmosphere learning, and evaluate learning outcomes from professional learning management through problem surveys and analysis, planning, implementation of plans, observation of school administrators and teachers' work performance, and reflection of work performance. Those involved in teaching and learning are given the opportunity to reflect on their work performance. of student teachers in schools and produce tangible results for learners. 2. The training curriculum based on the concept of professional learning communities to promote innovation in information and communication technology for student teachers consists of 6 components: 1) principles 2) objectives 3) content 4) methods used in training 5) media used in training 6) measurement and evaluation by implementing 5 steps of activities. The curriculum is very appropriate. The results of the pilot implementation (tryout) of the curriculum found that teachers organized professional learning higher than the 75 percent criteria set with statistical significance at the .05 level. 3. The results of the trial use of the curriculum after the training curriculum were found that teachers organized active learning at an excellent quality level and higher than the 75 percent criteria set with statistical significance at the level .05. 4. The results of the curriculum evaluation found that teachers' opinions on the training curriculum based on the concept of professional learning communities to promote innovation in information and communication technology for student teachers in terms of inputs, processes, and outputs were at the highest level overall.